Biodiversity impact assessment in road development in Lithuania - Vaiškūnaitė, Rasa; Mierauskas, Pranas; Špakauskas, Valdas (Transport, 2012)
Roads affect wildlife in different ways. Road construction increases fragmentation of habitats, influences landscape pattern and alters the physical environment. Roads act as barriers to animal movements, increase their mortality rates and cause other negative impacts on biodiversity. The current paper overviews the assessment of road impacts in Lithuania, reviews approaches applied to evaluation of road development impacts as well as analyses application of Lithuanian legal documents in the field. In Lithuania, assessment of possible effects inflicted by envisaged road construction is determined by the Law on Environmental Impact Assessment of Planned Economic Activities and orders of the Ministry of Environment. Although the legislation covers some aspects of biodiversity, little attention is given to the assessment of the impact on biodiversity; meanwhile the impact assessment of proposed economic activities on Natura 2000 sites is clarified more extensively. Lithuanian methodological guidelines on determination of environmental impact assessment procedures and principles for the road network do not comply with international requirements concerning the biodiversity impact assessment of roads. The practiced biodiversity impact assessment used for road development projects in Lithuania complies with minimum requirements used in developed countries. To fulfil international requirements on biodiversity conservation, it is necessary to amend the Lithuanian legislation on environmental impact assessment and issue guidelines on biodiversity protection in road development projects. The article proposes models for calculation of road pollution dispersion for evaluation of air quality next to the already existing and newly projected roads. First Published Online: 26 Jun 2012